ERGENLERDE ALGILANAN ANNE BABA TUTUMU İLE MADDE BAĞIMLILIĞI ARASINDAKİ İLİŞKİNİN İNCELENMESİ. - OĞUZ, Fatma; ÖĞRETİR ÖZÇELİK, Ayşe Dilek (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2018)
The aim of this study is to examine the relationship between 17-18 aged adolescents' drug abuse level and child raising style. This study aims to give notable contribution to substance abuse literature in our country. The sample of the study consists of 201 students (100 women, 101 men) from 4 different high schools in Çermik county of Diyarbakır. Personal Information Form, Child Raising Styles Scale and Binding Styles Scale developed by the researchers were used to collect data in the research. SPSS (Statistical Package for Social Sciences) 21.00 statistical package program is used to analyze hypothesis of the research. Correlation, regression, and t-test methods are used via package program. According to the findings of the research, one third of the respondents used addictive substances and the gender distribution was 59.4% male, 7% female. When the relationship between substance abuse and parental attitude was examined, the substance use rate of the children of the supervised families was higher at a significant level, while the substance use rate of the adolescents at the acceptance / interest level was lower at a significant level.